An Economic Study of Retreating Longwall Mining Versus Bord and Pillar Mining on the South Coast of New South Wales (The Australasian Institute of Mining and Metallurgy, 1980)
This paper describes the economic study of longwall versus bord and pillar mining using all continuous miners for a colliery located at the South Coast district of New South Wales, Australia. In this district longwall mining appears to be a better economic proposition than bord and pillar. The internal rate of return on investment is found to remain approximately constant for each method irrespective of life. The economic importance of percentage extraction of coal is shown to be small for high values of minimum rates of return, becoming more significant as the minimum rate of return decreases.